Novel Pyrimidine Associated Thiazolidines: Design, Synthesis, Characterization and Evaluation as Antibacterial Agents - Reddi Maddireddi, Chandra Sekhara; Parimi, Uma Devi; Bhimi Reddy, Sreenivasa Reddy; Kasapu, V.V.V. Satyanarayana (Asian Journal of Chemistry, 2017)
Several novel pyrimidine associated thiazolidines (5a-f) have been synthesized by using 6-trifluoromethyl-pyrimidine-4-ol (1) as starting material and by participating (6-trifluoromethylpyrimidine-4-yloxy)acetic acid ethyl ester (2) (6-trifluoromethyl-pyrimidine-4-yloxy)acetic acid hydrazide (3) and (6-trifluoromethyl-pyrimidine-4-yloxy)acetic acid benzylidene-hydrazides (4a-f) as intermediates through substitution, condensation and cyclization. The chemical structures of all the newly synthesized compounds were confirmed by IR, 1H and 13C NMR, mass spectral studies and elemental analysis. Further, the synthesized products were screened for their antibacterial activity and the zone of inhibition was measured.